Low back pain with impact at 17 years of age is predicted by early adolescent risk factors from multiple domains: Analysis of the Western Australian Pregnancy Cohort (Raine) Study - Smith, Anne; Beales, Darren; O'Sullivan, Peter; Bear, N.; Straker, Leon (2017)
Copyright © 2017 Journal of Orthopaedic & Sports Physical Therapy®. Study Design: Prospective cohort study of the Western Australian Pregnancy Cohort (Raine) Study. Background: Low back pain (LBP) commonly develops in adolescence and is a significant risk factor for adult LBP. A broad range of factors have been associated with the development of adolescent LBP, but prior literature has limitations related to characterization of LBP and the scope of risk factors considered. Objective: This study aimed to identify potential factors contributing to the development of LBP, with and without impact, at 17 years of age, utilizing a broad range of exposures at 14 years of age. Methods: Data from 1088 participants (52.1% female) with "no LBP," "LBP with minimal impact," and "LBP with impact" at 17 years of age and a range of measures from multiple domains, including spinal pain, physical, psychological, social, and lifestyle, at 14 years of age were collected for the study. Multivariable multinomial logistic regression was used to estimate the association of potential mechanistic factors at 14 years of age with LBP at 17 years of age. Results: Female sex and back pain at 14 years of age were strongly associated with LBP at 17 years of age. Potential mechanistic factors for LBP outcomes at 17 years of age included exposures from the pain (neck/shoulder pain) and physical domains (standing posture subgroup membership, back muscle endurance, throwing distance), psychological domain (somatic complaints, aggressive behavior), social domain (socioeconomic area), and lifestyle domain (exercise out of school). Conclusion: The findings support the multidimensional nature of adolescent LBP and highlight the challenge this presents for epidemiological research, clinical practice, and prevention initiatives in the general population. Level of Evidence: Prognosis, level 1b.